2015
DOI: 10.1103/physreve.91.023203
|View full text |Cite
|
Sign up to set email alerts
|

Stability of optical solitons in parity-time-symmetric optical lattices with competing cubic and quintic nonlinearities

Abstract: The existence and stability of optical solitons in the semi-infinite gap of parity-time (PT)-symmetric optical lattices with competing cubic and quintic nonlinearities are investigated numerically. The fundamental and dipole solitons can exist only with focusing quintic nonlinearity; however, they are always linearly unstable. With the competing effect between cubic and quintic nonlinearities, the strength of the quintic nonlinearity should be larger than a threshold for the solitons' existence when the streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The PT symmetric potential requires a complex conjugation, which means that the refractive index and gain-loss (corresponding to the real and imaginary parts of the PT symmetric potential) distributions in an optical medium with PT symmetry are even and odd [4], respectively. This structure can be obtained by setting a special distribution of the refractive index and gain-loss in the medium, which has led to a lot of novel physical phenomena and applications [3][4][5][6][7][8] * Author to whom any correspondence should be addressed. in linear and nonlinear optics regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PT symmetric potential requires a complex conjugation, which means that the refractive index and gain-loss (corresponding to the real and imaginary parts of the PT symmetric potential) distributions in an optical medium with PT symmetry are even and odd [4], respectively. This structure can be obtained by setting a special distribution of the refractive index and gain-loss in the medium, which has led to a lot of novel physical phenomena and applications [3][4][5][6][7][8] * Author to whom any correspondence should be addressed. in linear and nonlinear optics regions.…”
Section: Introductionmentioning
confidence: 99%
“…in linear and nonlinear optics regions. In particular, numerous studies have been conducted on nonlinear materials with PT symmetries such as the soliton solution and stability in a Gaussian potential [5], the control of soliton in nonlinear medium with a PT symmetric potential [6][7][8]. However, these works mainly focus on the scalar beam with uniform polarization.…”
Section: Introductionmentioning
confidence: 99%
“…The MI of waves in the PT -symmetric nonlinear Schrödinger (NLS) equation has been widely studied too [51,[72][73][74][75][76][77]. As an extension of the studies in this direction, constant-amplitude (CA) waves have recently been addressed in models with more general complex potentials [78].…”
Section: Introductionmentioning
confidence: 99%
“…[14,15] Desyatnikov et al and Ge found STSs in an optical media with higher order nonlinearities. [16,17] Mihalache et al obtained stable spinning STSs by tuning the focusing and defocusing nonlinearities. [18] Zhang et al revealed that 3D solitons can stably exist in atomic systems with spinorbit coupling interactions.…”
mentioning
confidence: 99%